Erraldoi berekoia ; Lamina ezkongaia / [egokitzailea, Iñaki Zubeldia ; marrazkilariak, Marcos San Blas, Iñaki Garmendia] - Zubeldia, Iñaki (Plisti (Ibaizabal), 2002)
Haurrak irakurtzen trebatzeko ipuinak